2011
DOI: 10.1016/j.jhep.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation using fatty livers: Always feasible?

Abstract: Steatotic liver grafts represent the most common type of "extended criteria" organs that have been introduced during the last two decades due to the disparity between liver transplant candidates and the number available organs. A precise definition and reliable and reproducible method for steatosis quantification is currently lacking and the potential influence of the chemical composition of hepatic lipids has not been addressed. In our view, these shortcomings appear to contribute significantly to the inconsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
243
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(258 citation statements)
references
References 75 publications
9
243
1
5
Order By: Relevance
“…6 The increasing prevalence of NAFLD and in particular NASH in prospective donors diminishes the availability of organs in future. 7 Apparently 15-20% of the western population is obese, with up to 80-90% obese patients affected with NAFLD. Approximately 10-25% of these NAFLD patients develop NASH, whereas about 2-3% of the general population is estimated to have NASH.…”
mentioning
confidence: 99%
“…6 The increasing prevalence of NAFLD and in particular NASH in prospective donors diminishes the availability of organs in future. 7 Apparently 15-20% of the western population is obese, with up to 80-90% obese patients affected with NAFLD. Approximately 10-25% of these NAFLD patients develop NASH, whereas about 2-3% of the general population is estimated to have NASH.…”
mentioning
confidence: 99%
“…Cirrhosis develops in up to 35% of those cases with a risk of liver failure or HCC. 11 Therefore, the increasing prevalence of NAFLD is expected to raise the number of liver transplantation (LT) candidates in the near future, and possibly become the most common indication for LT. 3 Risk factors: Given the tight association with MetS, the whole spectrum of NAFLD mostly occurs in patients with obesity (60-95%), T2DM (28-55%), and hyperlipidemia (27-92%). In a study of patients undergoing bariatric surgery, NAFLD was found in up to 95%, with fibrosis in 74%, and mild necroinflammation in 24% of cases.…”
Section: Definitionmentioning
confidence: 99%
“…However, several transplant programs consider a liver biopsy as mandatory before discarding a potential liver graft. 3 It was well recognized that the implantation of a donor's liver with severe fatty infiltration (>60%) is frequently associated with an increased incidence of postoperative complications. In the past, grafts with ≥30% fatty infiltration are not acceptable for transplantation.…”
Section: Impact Of Steatosis On Ltmentioning
confidence: 99%
See 2 more Smart Citations